Preliminary Design of Traditional Fishing Boat (2 GT) With Additional Floating Compartment for Safety Reasons Using BKI Rules - Irfan Wahyudin; Yeddid Yonatan Eka Darma; I.G.N.A Satria Prasetya; Hery Inprasetyobudi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Traditional fishing boats are used by fishermen for finding fish to support their daily lives. Because there are many shortcomings in their boats (design problems) and natural conditions that often change, accidents can occur which cause their boats to easily overturn and sink to the bottom of the sea. Other problems were also encountered, such as the boat's obstacles, and the boat's floating compartment was not well designed. For this reason, the author conducted research on the design of a fishing boat with a floating compartment using the BKI rules. Using one of the existing boats was made as a design reference with boat sizes. The principal dimension of the fishing boat is LOA: 10.15 m, Lwl: 8,996 m, B: 1 m, H: 0.87 m, H: 0.3 m, and 2 GT. The results of the calculations find that the engine specification that suits the fishing boat is 3.5 kW with a speed of 7 knots. The author's research varies the Floodable Length of the original boat's floating compartment with a compartment size of 1.365 m AP, 1.325 m FP, and model 2 floating compartment using BKI rules with AP size 2.225 m and FP 2.425 m. The analysis result based on the design of the fishing boat shows that model 2 is the best design. Construction in accordance with BKI regulations, a mixed type of construction was chosen. The frame distance is 500 mm with the stiffener type model h = 25 mm, bb = 30 mm, and bc = 36 mm. Meanwhile, the total stringer is 6 stiffeners.